Determinant Factor of Compensation Toward Job Performance of Teachers and Staff at Islamic Junior High School - Mardalena, Mardalena; Sarinah, Sarinah; Taufan, Ade; Melina, Angra; Yunus, Mukhlis; Saukani, Saukani; Hayati, Hayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The aim of the study was to find out whether there is a correlation between compensation and the performance of teachers and staff at MTs Syekh Maulana Qori. This study uses a quantitative approach with a type of correlational. The population in this study were all teachers and staff at MTs Syekh Maulana Qori, with a total of 15 people. The sampling technique used was purposive sampling technique so the sample used in this study was the entire MTs Syekh Maulana Qori staff, totaling 15 people. The main research data were obtained from respondents' questionnaire answers which were constructed from each indicator of the two research variables. After the data is declared normal and homogeneous then the research is continued. In order to answer the research hypothesis, a T-test was carried out by considering the value of T count and the value of sig. The results of the analysis showed that the t count value was 3.332 > t table 2.131 and the sig. 0.47 < 0.05, which means that H0 is rejected and Ha is accepted, which also means that there is a positive and significant effect of compensation on the performance of teachers and staff of MTS Syekh Maulana Qori. The results of the study also obtained an R square value of 0.795 or 79.6% compensation can contribute to the performance of teachers and staff of MTs Syekh Maulana Qori. So that compensation is highly recommended to be considered and carried out in order to provide a sense of justice for teachers and staff who have dedicated themselves to MTs Syekh Maulana Qori. Of course, their performance will have a direct, both positive and negative impact on student achievement.